Lymphoproliferative Disorders in Inflammatory Bowel Disease Patients: Is It the Drugs or the Disease - Bernardes,Carlos (2018)
Introduction: Systemic inflammatory diseases are related to an increased risk of lymphoproliferative disorders. Although inflammatory bowel disease (IBD) was also associated with these conditions, population-based studies failed to demonstrate this relationship, and most studies only identified a very small number of cases. In the last few years, concerns arose regarding the role of thiopurines and tumour necrosis factor-alpha (TNF-α)-blocking agents in the development of lymphoma, influencing therapeutic decisions in IBD patients. The aim of this study was to describe a case series of IBD patients who developed a lymphoproliferative disorder in our tertiary referral centre. Material and Methods: The clinical records of all IBD patients who were observed in our unit between January 2007 and December 2016 were retrospectively reviewed, and IBD subjects who were diagnosed with a lymphoproliferative disorder were selected. Clinical and demographic data regarding both conditions were collected. Results: Six IBD patients were diagnosed with a lymphoma - 4 Hodgkin lymphomas and 2 B-cell non-Hodgkin lymphomas - of which 3 corresponded to primary colonic lymphomas. Immunohistochemical analysis detected the presence of Epstein-Barr virus in the tumour cells of 2 patients, both of them with Hodgkin lymphomas. Only 2 patients were previously treated with thiopurines or anti-TNF-α drugs; none of the remaining had any history of immunosuppressive treatment. Discussion and Conclusions: Despite major attention being currently focused on the effect of treatment, which may play the main role in the increased susceptibility to lymphoma in IBD patients, and although it may be difficult to demonstrate, IBD itself may contribute to the development of lymphoproliferative disorders, particularly primary intestinal lymphomas.